2013
DOI: 10.1016/j.rmed.2013.04.014
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to long-term respiratory care: Results of a community-based post-rehabilitation maintenance program in COPD

Abstract: A community-based maintenance exercise program is feasible and can successfully preserve exercise capacity and health-related quality of life following institutionally-based PR in patients with moderate to severe COPD. A more formal evaluation of this approach is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 33 publications
3
28
1
2
Order By: Relevance
“…Previous studies have reported similar preferences for delivering educational intervention programs, including web-based methods, use of text messaging, and video formats [39]; however, challenges akin to those identified in this study were also noted, such as difficulty navigating websites or using available technology [40, 41]. In addition, patients and family members in this study strongly recommended aligning new programs with existing programs within communities; this is consonant with literature showing that health promotion programs which are developed in collaboration with a community-based organization tend to enjoy high participation rates [42, 43]. …”
Section: Discussionsupporting
confidence: 67%
“…Previous studies have reported similar preferences for delivering educational intervention programs, including web-based methods, use of text messaging, and video formats [39]; however, challenges akin to those identified in this study were also noted, such as difficulty navigating websites or using available technology [40, 41]. In addition, patients and family members in this study strongly recommended aligning new programs with existing programs within communities; this is consonant with literature showing that health promotion programs which are developed in collaboration with a community-based organization tend to enjoy high participation rates [42, 43]. …”
Section: Discussionsupporting
confidence: 67%
“…This is consistent with previous findings over 18–24 months . This clinical decline over the longer term may be due to reduced adherence to ongoing exercise, with difficulty in transitioning from institution‐based rehabilitation . The lack of a positive approach to exercise may also impair adherence .…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, individuals enrolled in the program had moderate to severe COPD (Table 1) and participated successfully with no adverse events without direct supervision from a health-care professional. 12 Participants expressed many positive experiences relating to community center staff and reported feeling safe as a result of their presence, in addition to other members of the community center. As the case manager was affiliated with the PR institution, the participants still felt part of the hospital community although they had successfully transitioned to a community setting, overcoming previously cited gaps in maintenance care.…”
Section: Discussionmentioning
confidence: 99%